Research on process-oriented standard requirements generation technique for equipment research & development - WANG Changxi; TANG Wei; LIU Qiguo; ZHANG Xiaoming (Xibei Gongye Daxue Xuebao, 2023)
Standard requirement generation method is a core technique of standard formation. Due to the lack of systems approach, missing of standard technical elements, weak correlation between standards and research and development(R & D) activities are appeared frequently. Deficiencies in integrity, applicability and traceability of standards can be observed noticeably, which makes the equipment standards cannot bring into full play of cost reduction and efficiency improvement, cannot promote the equipment technology development effectively. According to the positive development requirements of independent and controllable standards, an activity-based standard requirement capture scene model is defined, a mechanization of standard requirement identification is described, a standard configuration, standard element definition and standard requirement integration methods are provided, a mapping matrices of activities, tools, database and standard requirement are established, a process-oriented standard requirements generation method for equipment R & D is finally proposed. By applying in aircraft engine compressor aerodynamic design field, the proposed method shows that the effectiveness of the building relationships between the standards and equipment R & D activities, which can ensure the integrity, availability and uniqueness of standard requirements, support equipment standard systems independent and controllable development.